EMPOWERMENT OF MAULID AL-BARZANJI READING TRADITION FOR YOUTH IN SUTAWINANGUN VILLAGE - ayunuraeni; Alni Pebriani Awdiyanti; Sekarsari; Deden Hasan Majid; Sofandi (UI Cirebon (Universitas Islam Cirebon), 2023)
This study aims to analyze community empowerment through a program proposed by PKK members in Sutawinangun village, namely barzanji reading training so that children and adolescents can participate in barzanji reading activities that have just been carried out at the Al Amanah mosque. This study uses observational and descriptive methods. A Sutawinangun village is a villeage located on the border of the city so that the social conditions of the community are very different from villages far from the city. One of them is the condition of the teenagers who lack religious morals. Therefore, researchers empower the tradition of reading barzaji to get to know Islamic traditions in Indonesia and foster love for the Prophet Muhammad. The method is the observation of the teenegers of Sutawinangun and interviews with local community leaders. The enthusiasm of children and adolescents so that in a short time children and adolescents have been able to sing poems and praises in al-Barzaji's birthday and are able to play Islamic music to accompany the readers of al-Barzanji's birthday.